Syriac Noun and Verb Paradigms in the Eastern Pronunciation (Chaldean) - Anonymous, Anonymous (Analecta Gorgiana, 2010)
This handbook for grammatical forms in Syriac provides students and scholars with a quick reference for the various forms of nouns, pronouns, and verbs, and also offers a simple way to learn Syriac grammatical terminology